2018
DOI: 10.1590/0102-7786331012
|View full text |Cite
|
Sign up to set email alerts
|

Distribuições de Tendências Sazonais de Temperatura Média e Precipitação nos Biomas Brasileiros

Abstract: Resumo O objetivo deste trabalho foi identificar tendências climáticas em séries temporais de precipitação pluviométrica acumulada mensal e de temperatura média do ar mensal, nas quatro estações do ano, registradas em 243 localidades distribuídas pelos biomas do Brasil. Os dados foram extraídos do Instituto Nacional de Meteorologia (INMET). Aplicaram-se os testes estatísticos de Mann-Kendall e de Pettitt. Os resultados estatísticos e os mapas de distribuições de tendências sazonais permitem observar que todos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…This biome covers important aquifers and rivers [2] and is located in the central area of the country, being the origin of large hydrographic regions in Brazil and in the South American continent [3,4]. However, Lee et al [5], Debortoli et al [6] and Penereiro et al [7] reported reduction of approximately 70 mm in annual precipitation in the Cerrado region between 1979 and 2006, indicating an extension of the dry season. Furthermore, although with great biological diversity, the biome is under continuous threat of extinction due to the expansion of agriculture and pastures, as occurs with other biomes [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…This biome covers important aquifers and rivers [2] and is located in the central area of the country, being the origin of large hydrographic regions in Brazil and in the South American continent [3,4]. However, Lee et al [5], Debortoli et al [6] and Penereiro et al [7] reported reduction of approximately 70 mm in annual precipitation in the Cerrado region between 1979 and 2006, indicating an extension of the dry season. Furthermore, although with great biological diversity, the biome is under continuous threat of extinction due to the expansion of agriculture and pastures, as occurs with other biomes [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…The result of the Mann-Kendall Seasonal test indicated that, for most of the monitoring stations (78%), there was no significant rainfall trend (p-value> 0.05) (Figure 6). The prominent absence of a significant trend in pluviometric data was also observed by Penereiro et al (2018), when analyzing Brazilian municipalities located in several biomes. The authors specified that of the 70 municipalities studied in the Cerrado, 60 did not show significant trends of either reduction or increase.…”
Section: /13mentioning
confidence: 54%
“…The collection areas are about 1.500 km away and differ in vegetation and annual average temperatures. The Pampa biome has more challenging periods of low rainfall than the Atlantic Forest, which is known to be humid (PENEREIRO et al, 2018). Perhaps, this relationship between the selective pressure of the environment on kidney morphology can play a role in understanding the differences found in renal dimensions between the two populations.…”
Section: Discussionmentioning
confidence: 99%